“The effect of combining the strategies of idea gardens and the visual approach in developing artistic imagination skills among second-year intermediate schoolgirls”. (Journal of the College of Basic Education, 2024)
The research aimed to identify “(The effect of combining the strategies of idea gardens and the visual approach in developing the artistic imagination skills of second-year intermediate schoolgirls”.).” The researcher used the experimental method and chose an experimental design with partial control, the researcher took a sample from the Directorate of Al-Rusafa First Education / Intermediate (Al-Ansam), the amount of the experimental group, division (B), is (31) female students, and the control group, division (A), is (30) female students, the researcher prepared a test for artistic imagination skills, numbering (12), and after conducting psychometric properties on the test and ensuring its validity and reliability, the researcher applied the test, used statistical methods appropriate for the research, and showed the result. (There is a statistically significant difference in favor of the experimental group over the control group).